Student Cyberloafing Behavior in the Learning Process: A Comparative Study - Suci Habibah; Fitra Herlinda; Uswatun Hasanah; Rusnila; Syafrizal (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Cyberloafing in the learning process is the behavior of using the internet during study hours for personal interests that are not related to learning. This needs to be addressed immediately because it will have an impact on decreasing motivation, concentration, achievement and even failure in learning. This study aims to analyze differences in cyberloafing based on gender and semester level. This research method is quantitative descriptive, comparative descriptive type with a factorial model design. The population in this study was 185 students of Islamic Education Guidance and Counseling, sampling using total sampling. The data collection tool used in this research is a cyberloafing scale with a Likert model scale of 45 valid statement items and the reliability level of the cyberloafing scale instrument has a Cronbach Alpha value of 0.742. The results of this study found that there was no significant difference in students' cyberloafing levels between men and women. There is a significant difference in the level of cyberloafing of students at semester levels II, IV and VI. There is an interaction between the variables gender and semester level in explaining student cyberloafing.